Species-Specific Mytilus Markers or Hybridization Evidence? - Guzman-Rojas, H (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The development of molecular methods to detect Mytilus hybrids is important for food authentication, conservation, and the sustainable management of shellfish aquaculture as accurate food labeling is a legal requirement, and because introgression may promote undesirable phenotypes or displace native species. However, nuclear and mitochondrial markers can segregate independently, compromising diagnostic congruence between these markers. This study aimed to detect hybrids in the Mytilus edulis species complex using a multi-locus approach, including RFLP-PCR assays for Me 15/16, 16S rRNA, and COIxba, in samples collected from five continents. We used a model-based Bayesian method for hybrid and pure species detection to analyze the diagnostic potential of nuclear and mitochondrial markers in mussel samples from South America, North America, Africa, Oceania, and Europe. Our results showed that the combined use of markers can differentiate between M. trossulus, M. edulis, M. galloprovincialis, and M. chilensis. The combined use of nuclear and mitochondrial molecular markers also improves hybrid detection and allows us to identify introgression using Bayesian analysis. © 2025 by the authors.